2020
DOI: 10.1101/2020.04.17.20067348
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Massive and rapid COVID-19 testing is feasible by extraction-free SARS-CoV-2 RT-PCR

Abstract: Coronavirus disease 2019 (COVID-19) is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The most widely used method of COVID-19 diagnostics is a reverse transcription quantitative polymerase chain reaction (RT-qPCR) assay, detecting the presence of SARS-CoV-2 RNA in patient samples, typically from nasopharyngeal swabs. The RNA extraction is a major bottleneck in current COVID-19 testing, in terms of turn-around, logistics, component availability and cost, which delays or completely p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(109 citation statements)
references
References 13 publications
3
105
0
1
Order By: Relevance
“…This approach can be employed as rapid and economical method for diagnosis which does not require any RNA extraction step. Our results are in line with the earlier reports of RNA extraction-free RT-PCR (Alcoba-Florez et al, 2020;Bruce et al, 2020;Smyrlaki et al, 2020), but here we have done a very extensive (n=40) and thorough standardization of this procedure which is now consistent and compelling.…”
Section: Resultssupporting
confidence: 92%
“…This approach can be employed as rapid and economical method for diagnosis which does not require any RNA extraction step. Our results are in line with the earlier reports of RNA extraction-free RT-PCR (Alcoba-Florez et al, 2020;Bruce et al, 2020;Smyrlaki et al, 2020), but here we have done a very extensive (n=40) and thorough standardization of this procedure which is now consistent and compelling.…”
Section: Resultssupporting
confidence: 92%
“…Several groups are optimizing workarounds to avoid the RNA extraction step for PCR based SARS-CoV-2 testing while maintaining sensitivity 13,15,17,29 . Here, we have demonstrated a variety of saliva pre-treatment protocols that enable sensitive detection of SARS-CoV-2 by both RT-LAMP and qRT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…We found that a 30-minute incubation provided a more reliable readout. To neutralize or otherwise reduce inhibitors in human saliva, we tested several approaches that have been demonstrated to improve viral RNA detection in crude samples including saliva [13][14][15][16][17] . We tested simple dilution of particle-containing saliva into water, and various heat and chemical treatments.…”
Section: Reaction Optimization In Simulated Samplesmentioning
confidence: 99%
“…Hence the RT-nPCR test was able to detect presence of all three samples in a pool of 1:5. Direct testing of samples by RT-qPCR without RNA isolation has been described in recent reports (Bruce et al, 2020;Merindol et al, 2020;Smyrlaki et al, 2020). We performed direct testing of heat inactivated positive samples by the RT-nPCR test.…”
Section: Pooled and Direct Testingmentioning
confidence: 99%